1997
DOI: 10.1139/z97-097
|View full text |Cite
|
Sign up to set email alerts
|

Estimating sex ratios of loggerhead turtles in Brazil from pivotal incubation durations

Abstract: A method of estimating natural sex ratios of hatchlings of species with temperature-dependent sexual differentiation from data on incubation durations is described. The method was applied to loggerhead turtles (Caretta caretta) nesting in Brazil. Data on incubation durations were collected from 11 nesting beaches monitored for up to six seasons. It was estimated that 82.5% of the loggerhead hatchlings produced were female. The strongly female-biased sex ratio in Brazil is similar to that found. previously for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
141
0
22

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(170 citation statements)
references
References 29 publications
7
141
0
22
Order By: Relevance
“…Portanto, a maior duração da incubação no litoral sul da Bahia em relação aos dados registrados para a os ninhos da Praia do Forte, pode levar a uma maior produção de filhotes machos. A duração de incubação que gera 50% de machos e 50% de fêmeas, denominada duração pivotal, foi estimada em 59,3 dias para C. caretta (Marcovaldi et al 1997) e em 62,8 dias para E. imbricata , em estudos realizados com as populações do norte da Bahia. Embora a duração média da incubação na área de estudo tenha sido inferior à duração pivotal, ela é maior do que a duração no litoral norte da Bahia.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Portanto, a maior duração da incubação no litoral sul da Bahia em relação aos dados registrados para a os ninhos da Praia do Forte, pode levar a uma maior produção de filhotes machos. A duração de incubação que gera 50% de machos e 50% de fêmeas, denominada duração pivotal, foi estimada em 59,3 dias para C. caretta (Marcovaldi et al 1997) e em 62,8 dias para E. imbricata , em estudos realizados com as populações do norte da Bahia. Embora a duração média da incubação na área de estudo tenha sido inferior à duração pivotal, ela é maior do que a duração no litoral norte da Bahia.…”
Section: Discussionunclassified
“…De fato já foi verificado que nas áreas de nidificação de C. caretta no litoral do Espírito Santo as durações médias da incubação são mais altas do que no litoral norte da Bahia, resultando em uma maior produção de filhotes machos (Baptistotte et al 1999). O litoral norte da Bahia é a principal área de nidificação de C. caretta e E. imbricata no Brasil e cerca de 90% dos filhotes nascidos nestas áreas são fêmeas (Marcovaldi et al 1997. Portanto, áreas localizadas mais ao sul e com durações médias da incubação maiores -e, portanto, temperaturas de incubação mais baixas -, como é o caso do litoral do Espírito Santo, para C. caretta, e do litoral sul da Bahia, para C. caretta e E. imbricata, são áreas relevantes para a conservação, visto que auxiliam na manutenção da saúde demográfica das populações dessas espécies que se reproduzem no Brasil.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Hatching success of P. unifilis depended directly on the nesting period and the height of the nest in rela- Table 3 (Spotila et al, 1987;Eendebak, 1995;Marcovaldi et al, 1997). Both higher and lower incubation temperatures can cause embryonic death (Krause et al, 1982;Wilson, 1998;Valenzuela, 2001).…”
Section: Factors Related To Hatching Successmentioning
confidence: 99%
“…Several investigators have reported that the incubation duration in turtles is negatively correlated with the incubation temperature (Ewert et al, 2004;Valenzuela, 2001). The incubation duration is considered the easiest and least invasive method to estimate the sex ratio of the sea turtle hatchlings because the definition of their sex depends on environmental conditions (Marcovaldi et al, 1997;Mrosovsky et al, 1999). In turtles, low temperatures induce low metabolic activity, longer incubation durations, and a greater proportion of males.…”
Section: Introductionmentioning
confidence: 99%